Tools of the popularization of advertorial information in the modern press - Kitsa, Mariana O. (Journal of the Belarusian State University. Journalism, 2019)
In the article it is analyzed the theoretical aspects of creating quality advertising texts that draw the audience’s attention, defined the value of advertising mentality of consumers in the perception of advertising. It is also made the comparative analysis of the compliance of advertising in Ukrainian press councils foreign advertisers. It is also considered advices of foreign advertisers about how to create effective advertising messages. The article explains that an important role in promoting of advertising play the psychological characteristics of the audience to which the advertisement is spread. It is also explored the needs to consider these characteristics when creating advertising messages. The article shows that an important role in the perception of print advertising plays himself the title of an advertising appeal. There are analyzed the advices of foreign advertisers, and in the result it is summarized the rules to take seriously the title of the advertising message in the media, because it is proved that it is recited five times more than advertising appeal itself. The paper made a conclusion that, in order to increase the popularity of advertising in the press, it is necessary to take into account a combination of factors.